Prof. Dr. Dusko Bjelica's Articles Published in Sport Mont Journal: A Content Analysis - Ivan Vukovic (Journal of Anthropology of Sport and Physical Education, 2018)
Sport Mont Journal (SMJ) is a print and electronic scientific journal aims to present easy access to the scientific knowledge for sport-conscious individuals using contemporary methods. SMJ is published three times a year by the Montenegrin sport academy (MSA), in february, june and october of each year. SMJ publishes original scientific papers, review papers, editorials, short reports, peer review - fair review, as well as invited papers and award papers in the fields of sports science and medicine, as well as it can function as an open discussion forum on significant issues of current interest. SMJ covers all aspects of sports science and medicine, all clinical aspects of exercise, health, and sport, exercise physiology and biophysical investigation of sports performance, sports biomechanics, sports nutrition, rehabilitation, physiotherapy, sports psychology, sports pedagogy, sports history, sports philosophy, sports sociology, sports management and all aspects of scientific support of the sports coaches from the natural, social and humanistic side. Professor Bjelica is the editor-in-chief of this reputable magazine. He has also published works on it from 2004 to 2017 and published 65 papers. They are from various fields from the sphere of sports sciences. Among them he mostly dealt with football, sports training, biomechanics, physical education of children, nutrition and many others. This professor has obtained a lot of awards because of his great and hard work.